Analyzing Elementary School Students' Misconceptions in Number Sense Using a Five-Tier Diagnostic Test - Fauziah, Anna; Pandra, Viktor (Jurnal Riset Pendidikan Matematika, 2024)
Misconceptions related to the concepts underlying number sense represent one of the primary challenges faced by elementary school students in learning mathematics. This research analyzed the specific misconceptions encountered by elementary school students in Lubuklinggau, Indonesia, in relation to number sense, utilizing a five-tier diagnostic test. This qualitative descriptive study involved 28 Year 8 students from one of the Islamic School in Lubuklinggau who had previously studied number operations. Data collection was conducted using a five-tier diagnostic test and interviews. Data validity was ensured through triangulation. After administering the diagnostic test, the researchers cross-checked data through interviews and documentation. The data was analyzed in three stages: data reduction, data presentation, and data verification. The results indicate that (1) 27.6% of students experienced misconceptions; (2) the most prevalent type of misconception was the process-object error (31.5%); (3) the highest incidence of misconceptions occurred with the fifth indicator of number sense, assessing the reasonableness of a calculation (48.5%); and (4) the primary causal factor contributing to students' misconceptions was their own reasoning (0.97%).